Just say no to postmortem drug dose calculations. Issue 5 (24th July 2021) - Maskell, Peter D.
Abstract: For years, a number of professional groups have warned forensic and clinical toxicologists against calculating an administered dose of a drug based on postmortem blood drug concentrations. But to date, there has been limited information as to how unreliable these dose calculations may actually be. Using amitriptyline as a model drug, this study used empirically determined pharmacokinetic variables for amitriptyline from clinical studies coupled with clinical overdoses (where the individual survived), and death case studies (ascribed to amitriptyline toxicity) in which the dose of amitriptyline was known. Using these data, standard pharmacokinetic equations, and general error propagation, it was possible to estimate the accuracy of calculated doses of amitriptyline, compared with the doses that were consumed. As was expected in postmortem cases, depending on the pharmacokinetic equation used, the accuracy (mean +128% to +2347%) and precision (SD ± 383% to 3698%) were too large to allow reliable estimations of the dose of amitriptyline consumed prior to death based on postmortem blood drug concentrations. This work again reinforces that dose calculations from postmortem blood drug concentrations are unreliable.